DIFFERENT APPROACHES TO THE COMPOSITE SENTENCES IN MODERN LINGUISTICS (Conferencea, 2022)
This article describes the semantic and structural types of composite sententences and taxemic approach to the "composite sentences" offered by G`.M.Hoshimov1, who has accordingly worked out a string of universal metaterms and metanotions for syntactical phenomenon.